Zoonotic parasites carried by invasive alien species in China - Guang-Li Zhu; Yi-Yang Tang; Yanin Limpanont; Zhong-Dao Wu; Jian Li; Zhi-Yue Lv (BMC, 2019)
Abstract Background The invasive alien species may lead to great environmental and economic crisis due to its strong capability of occupying the biological niche of native species and altering the ecosystem of the invaded area. However, its potential to serve as the vectors of some specific zoonotic pathogens, especially parasites, has been neglected. Thus, the damage that it may cause has been hugely underestimated in this aspect, which is actually an important public health problem. This paper aims to discuss the current status of zoonotic parasites carried by invasive alien species in China. Main body This review summarizes the reported zoonotic parasites carried by invasive alien species in China based on the Database of Invasive Alien Species in China. We summarize their prevalence, threat to human health, related reported cases, and the roles of invasive alien species in the life cycle of these parasites, and the invasion history of some invasive alien species. Furthermore, we sum up the current state of prevention and control of invasive alien species in China, and discuss about the urgency and several feasible strategies for the prevention and control of these zoonoses under the background of booming international communications and inevitable globalization. Conclusions Information of the zoonotic parasites carried by invasive alien species neither in China or worldwide, especially related case reports, is limited due to a long-time neglection and lack of monitoring. The underestimation of their damage requires more attention to the monitoring and control and compulsory measures should be taken to control the invasive alien species carrying zoonotic parasites.